Effect of crack flank holes on fatigue crack growth. (May 2023) - Neto, D.M.; Cavaleiro, N.; Sérgio, E.R.; Jesus, J.; Camacho-Reyes, A.; Antunes, F.V.
Highlights: Effect of holes along the crack flanks on the fatigue crack growth rate. Numerical study using the cumulative plastic deformation at the crack tip. Parametric study on the diameter of holes and the distance between them. Experimental results on a CT specimen to validate the numerical model. Abstract: The effect of drilling two symmetric holes along the crack flanks on the fatigue crack growth (FCG) rate was evaluated numerically. The FCG increases (decreases) when the crack tip is behind (ahead) the holes. This behaviour is enlarged both by increasing the diameter of the holes and by reducing the distance between them. This is consequence of the geometrical effect, which modifies the plastic zone size. Experimental work validated the numerical model, indicating that that cumulative plastic strain at the crack tip is an adequate crack driving force and that cyclic plastic deformation is the main damage mechanism of FCG.